TRANSLATION TECHNIQUES AND ACCURACY OF REPRESENTATIVE SPEECH ACTS IN GOING SEVENTEEN SUBTITLE - Denise Thea Maresca Rumekso; Septina Indrayani (Politeknik Negeri Jakarta, 2024)
This study explores the translation techniques and accuracy of subtitles in the variety web series Going Seventeen, concentrating on representative speech acts in the